Caracterização agronômica de acesso de Mentha piperita L. e seu cultivo em sistema hidropônico através de mudas de estaquia - Silva, Tamires Thassane Souza (Universidade Federal de São Carlos, 2022)
Mentha piperita L. (Peppermint) is a European hybrid originated from the crossing of M. spicata x M. aquatica. The plants of this species are propagated by cuttings and used for medicinal purposes, food and cosmetics. Its use is associated with the presence of essential oils rich in menthol, produced in the leaves, branches and inflorescences. The objective of this work was to carry through the agronomic characterization of accessions of M. piperita L. of the germoplasm bank of the Federal University of São Carlos and to analyze its culture in hydroponic system through cuttings produced by woody type. The experimental design used was complete randomized blocks in factorial scheme with three repetitions, the data analysis was of variance using the Sisvar® program (Ferreira, 1999) and the means were compared by the Tukey test at 5% probability. During the first stage of the experiment, agronomic characteristics of 31 accessions were evaluated, such as: plant height and diameter, width and length of the leaf lamina, number of primary branches, length of the branches with inflorescence, anthocyanin content, percentage of pubescence and flowering period. There was great variation in these characteristics among the accessions, especially for the flowering period. Those with late flowering were considered ideal for cultivation of economic interest in the extraction of essential oils considering also the agronomic characteristics related to the percentage of anthocyanin, presence of pubescence and number of tillers that together showed satisfactory results in the production of essential oils. In the second phase in hydroponic cultivation system, analyzing agronomic characteristics of the same accessions the results were satisfactory in relation to the production of fresh biomass of the aerial part and of the roots, that contributed for the presence of plants with high concentration of tillers being such important characteristics when the whole plant is used for commercialization. The mortality rate of the plants was null. Thus, there are new accessions with great potential to enter the industrial and consumer market with high capacity to obtain extraction of essential oils.
Agronomic characterization of Mentha piperita L. accession and its cultivation in a hydroponic system through cuttings seedlings
Keywords: Mentha; Caracterização agronômica; Estaquia; Hidroponia; Agronomic characterization; Cuttings; Hydroponics; CIENCIAS AGRARIAS::AGRONOMIA